Safety of SARS-CoV-2 vaccine in patients with autoimmune neurological conditions: A systematic review and meta-analysis - Fan Ning; Xiang-qi Cao; Qing-qing Wang; Zhu-yi Li; Zhe Ruan; Ting Chang (Heliyon, 2024)
Introduction: Risk of adverse effects and exacerbation in autoimmune neurological conditions (ANC)are frequently cited reasons for COVID-19 vaccine hesitancy. This study evaluates the ANC safety of COVID-19 vaccines in the real world. Methods: Electronic databases were searched to identify studies reporting the use of the COVID-19 vaccine in ANC. We selected studies that provided data on adverse effects and worsening conditions related to ANC after vaccination. The pooled incidence rates for various adverse effects, stratified for the disease category, dosage, and type of vaccine, were estimated. Results: Twenty-eight studies (31 vaccination cohorts) were included. The pooled incidence rate of general adverse events was 0.35 (95%CI, 0.27–0.43, I2 = 100 %). The pooled incidence rates of local injection reaction, fatigue, weakness, myalgia, fever, headache, and chills were 0.27 (0.18–0.36, I2 = 98 %), 0.16(0.11–0.21, I2 = 93 %), 0.15(0.00–0.31, I2 = 97 %), 0.13(0.08–0.19, I2 = 97 %), 0.11(0.07–0.15, I2 = 95 %), 0.11(0.07–0.16, I2 = 97 %), and 0.09 (0.03–0.16, I2 = 96 %), respectively. The pooled incidence rate of exacerbation adverse events was 0.05 (95%CI, 0.04–0.07, I2 = 84 %). Conclusion: According to available evidence, the administration of COVID-19 vaccines in individuals with autoimmune neurological disorders seems well-tolerated, with few reports of adverse events. Furthermore, exacerbation of autoimmune neurological conditions following vaccination appears to be infrequent.